Biobased plastics with insect‐repellent functionality. (9th March 2019) - Annandarajah, Cindu; Norris, Edmund J.; Funk, Ryan; Xiang, Chunhui; Grewell, David; Coats, Joel R.; Mishek, Danny; Maloy, Benjamin
Abstract : Natural insecticides/repellents, such as pyrethrum (derived from chrysanthemum plants), and insect repellent N, N‐ Diethyl‐meta‐toluamide (DEET) were added to poly(lactic acid) (PLA) fibers through extrusion and spray coating on the PLA fabrics. Contact irritancy assay (CIA) showed that DEET‐treated PLA fabrics caused the lowest relative escape response of mosquitoes with an escape frequency of 33.3% ± 3.3%, indicating that DEET was less effect compared with natural insecticides/repellents. This was followed by the extruded natural pyrethrum‐treated PLA fabric with an escape frequency of 80% ± 6.3%. Finally, the PLA fabrics spray‐coated with natural pyrethrum caused the highest escape frequency of 98.3% ± 1.7%. Thus, it was found that pyrethrum/PLA fabrics functioned as a mosquito repellent better than DEET/PLA fabrics. In addition, TGA and tensile testing results demonstrated that pyrethrum was sufficiently thermally stable to be extrusion compounded with PLA. GPC results showed that DEET promoted de‐polymerization of PLA when co‐extruded. The results demonstrated that pyrethrum can be a viable additive for PLA to produce fibers that function as mosquito repellent to produce temporary garments that are compostable. The potential use of the developed biobased fibers with natural insect repellents is for single use of personal protection equipment (PPE) garments. POLYM. ENG. SCI., 59:E460–E467, 2019. © 2019 Society of Plastics Engineers